Recognition subtests for the Repeatable Battery for the Assessment of Neuropsychological Status: Preliminary data in cognitively intact older adults, amnestic Mild Cognitive Impairment, and Alzheimer’s disease - Duff, Kevin (Clin Neuropsychol, 2020)
The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) has three delayed recall subtests (list, story, figure), but only one delayed recognition subtest (list). Since comparisons between delayed recall and recognition can be useful in clinical neuropsychology, the current study sought to develop and preliminarily examine two proposed new subtests for Form A of the RBANS, Story Recognition and Figure Recognition. A sample of older adults who were cognitively intact (n=48) or classified with amnestic Mild Cognitive Impairment (MCI, n=29) or mild Alzheimer’s disease (AD, n=24) were administered the RBANS and the two new recognition subtests. In the primary analyses, cognitively intact participants performed significantly better than the two memory-impaired groups on all twelve scores (one recall and three recognition [total, hits, false positive errors] for the list, story, and figure). For amnestic MCI and AD participants, they showed statistically comparable scores on 7 of the 12 variables, where those with MCI performed better than those with AD on the other five scores. Across the three groups, effect sizes were large (e.g., Cohen’s d=1.0 – 2.9). In secondary analyses, all of the List Recall and Recognition scores significantly correlated with one another, and this pattern was observed for all of the Story Recall and Recognition scores and most of the Figure Recall and Recognition scores. Although preliminary, these new recognition scores appear to provide useful information and may improve the sensitivity of the RBANS in identifying cortical/subcortical profiles in clinical and research settings.